Changes In The Murobak Gas Processing Plant In The Years Of Independence (Zien Journal of Social Sciences and Humanities, 2025)
In the years of independence, significant changes and modernization works were carried out at the Mubarak Gas Processing Plant. The increase in the plant's production capacity, the introduction of new technological processes, and the implementation of investment projects ensured the effective use of existing resources. The Mubarak Gas Processing Plant not only provided competitive products for the domestic market but also exported its products to foreign markets. The expanded activities of the plant played an important role in providing employment for the local population and contributed to the production efficiency and economic development. This article analyzes the development dynamics of the plant and its promising projects based on mutual support and annual indicators.